FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN KERJA PERAWAT DI PUSKESMAS MOMPANG KECAMATAN PANYABUNGAN UTARA KABUPATEN MANDAILING NATAL 2020 - Rudi Mulyadi; Mappeaty Mappeaty; Achmad Rifa’i (Jurnal Ilmu Keperawatan Indonesia, 2021)
Nursing services are assistance provided to individuals who are sick or healthy to be able to meet their needs as living things.Job satisfaction is someone's effective response to a job at the Mompang Community Health Center, the number of nurses until 2020 was 55 people.This study aims to analyze the factors of responsibility, job, salary / incentives, job security and job performance promotion that can affect job satisfaction of nurses at Mompang Health Center in the period from April to September 2020. This study is a case control study comparing satisfied and unsatisfied groups. satisfied, 30 respondents and 25 respondents were not satisfied.From the results of the study that the variable job responsibilities, incentive salaries, job security have a significant effect on the work of nurses. The responsibility factor with a sig value of 0.000 <0.013 and the workload factor of sig 0.000 <0.021, the factor of salary / incentive sig 0.000 <0.021, the factor of job security sig 0.000 <0.001 is the most dominant factor affecting the job satisfaction of nurses at Mompang Public Health Center, Kec. Panyabungan Utara Kab. Mandailing Christmas 2020.For the Health Office and puskesmas to increase attention to achieve job satisfaction for nurses.